Perbedaan kemampuan argumentasi siswa dengan penerapan argument mapping materi sistem sirkulasi ditinjau dari academic self efficacy - Nadia Salsabila; Dwi Oetomo; Muzzazinah Muzzazinah (Universitas Sebelas Maret, 2023)
ENThis study aims to (1) find out differences in students' argumentation abilities between learning using argument mapping media and not, (2) find out differences in students' argumentation abilities with different levels of academic self-efficacy, (3) find out interaction between mapping media arguments and academic self-efficacy on students' argumentation abilities. This research is quasi-experimental with a posttest-only pattern and nonequivalent design. The research was conducted at a High School in Boyolali for the 2022/2023 academic year. The instrument for argumentation skills uses an essay test, while for academic self-efficacy, students use a questionnaire with a Likert Scale of 1-4. Data analysis techniques for argumentation skills and academic self-efficacy use the two-way ANOVA test and the LSD (Least Significance Different) test. The results showed that: (1) There are differences in students' argumentation skills between learning by applying media argument mapping; the highest difference lies in the aspects of warrants and backing with a range of scores far enough between the experimental and control classes, namely 22.14 and 15.49 respectively, (2) There are differences in the argumentation abilities of students with different levels of academic self-efficacy. Students with high and moderate academic self-efficacy have better argumentation skills than students with low academic self-efficacy. (3) There is no interaction between media argument mapping and academic self-efficacy on students' argumentation abilities. Academic self-efficacy and media argument mapping have their effects on argumentation ability. IDPenelitian ini bertujuan untuk : (1)mengetahui perbedaan kemampuan argumentasi siswa antara pembelajaran yang menggunakan media argument mapping dan tidak, (2)mengetahui perbedaan kemampuan argumentasi siswa dengan tingkat academic self efficacy berbeda, (3)mengetahui interaksi antara media argument mapping dan academic self efficacy terhadap kemampuan argumentasi siswa. Penelitian ini merupakan penelitian quasi-experimental design dengan pola posttest only with nonequivalent design. Penelitian dilaksanakan di salah satu SMA Negeri di Boyolali Tahun Ajaran 2022/2023. Data kemampuan argumentasi siswa dikumpulkan menggunakan tes essay, sedangkan untuk academic self efficacy siswa menggunakan angket dengan Skala Likert 1-4. Teknik analisis data untuk kemampuan argumentasi dan academic self efficacy menggunakan uji ANOVA 2 jalur (two ways ANOVA) dan uji LSD (Least Significant Different). Hasil menunjukkan bahwa: (1) Terdapat perbedaan kemampuan argumentasi siswa antara pembelajaran dengan penerapan media argument mapping. Perbedaan tertinggi terletak pada aspek warrant dan backing dengan rentang skor cukup jauh antara kelas eksperimen dan kontrol, yakni masing-masing 22,14 dan 15,49, (2) Terdapat perbedaan kemampuan argumentasi siswa dengan tingkat academic self efficacy berbeda. Siswa yang memiliki academic self efficacy tinggi dan sedang memiliki kemampuan argumentasi yang lebih baik dibandingkan siswa dengan tingkat academic self efficacy rendah, (3) Tidak ada interaksi antara media argument mapping dan academic self efficacy terhadap kemampuan argumentasi siswa. Academic self efficacy dan media argument mapping memiliki pengaruh sendiri-sendiri terhadap kemampuan argumentasi.